Analisis Penggunaan Media Pembelajaran Wordwall Game dalam Pembelajaran Matematika di Sekolah Dasar - Ichda Nurul Marlita; Siti Patonah; Evy Ariestanti; Noor Miyono (Universitas Cokroaminoto Palopo, 2024)
This research was motivated by the lack of use of technology-based learning media in mathematics learning for class VA students at Sendangguwo 01 State Elementary School student learning activity was low and learning seemed monotonous so students were less enthusiastic about studying mathematics. This research aims to analyze the use of wordwall game-based learning media on students' mathematics learning activities. This research uses a qualitative descriptive research method. This research was carried out in the class of VA Sendangguwo 01 State Elementary School, with 27 students as research subjects. Data collection techniques used were observation and interviews. The data analysis used is data collection, data reduction, data presentation and conclusions. The results of the research prove that the word wall game learning media is an interactive media that is easy to use and in learning activities can make a good contribution as a form of supporting mathematics learning activities for class VA students at Sendangguwo 01 State Elementary School. So it can be concluded that the wordwall game media has become a technology-based media in the 5.0 era. which is easy to use, interesting and creates learning, especially in mathematics subjects so that it is effective in increasing student learning activities.